Benefits of Digital Wireless Technology for Persons with Hearing Aids - Thibodeau, Linda M.; Schaper, Lauren (Seminars in Hearing, 2014)
Wireless technology for persons with hearing loss began with cumbersome body-worn systems that nevertheless provided speech-recognition benefits in noisy environments. The first ear-level wireless systems were welcomed despite the awkward antenna that extended from the behind-the-ear case. The next-generation, removable, multichannel receiver provided a cost-effective means for school districts to maintain a stock of equipment to be used across students and classrooms. More recently, the advances have been less focused on physical size reductions and more focused on improvements to the signal quality in increasingly noisier environments. Two studies were designed to evaluate the new technological features by Phonak (Phonak, Warrenville, IL) known as adaptive FM and later adaptive digital processing. Each advance in technology resulted in greater gains in speech recognition in noise such that with the adaptive digital system, persons were able to achieve 48% correct in 80- decibels A weighted (dBA) noise levels. Persons with hearing loss using this technology are likely to hear more than persons with normal hearing in high-noise environments.
Keywords: Assistive technology; hearing impaired; FM technology; digital adaptive technology